Yield Test on Chlorella sp. Powder Extracted Using Different Solvents - Desi Lestari; Dian Iriani; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aims to determine the yield of Chlorella sp. powder extracted using different solventsbased on the degree of polarity. In extraction process, there were 3 solvents used, namely polar solvent (methanol 70%), semi-polar (ethyl acetate 80%), and non-polar (n-hexane 80%) with ratio sample:solvent 1:2 (w/v). The result showed that Chlorella powder extracted using polar solvent (methanol 70%) obtained the highest yield (30,17%), among other solvents ethyl acetate 17,31%, and n hexane 4,21%. Therefore, polar solvent (methanol 70%) is more optimal to extract Chlorella sp. powder. Keywords: Extraction, yield of Chlorella sp. Different solvents.